Abjection overruled! Time to dismantle sexist cyberbullying in academia. (January 2023) - Mandalaki, Emmanouela; Pérezts, Mar
In this essay, we draw on a personal experience of sexist cyberbullying unleashed, on social media, against one of our academic papers, to act up against increasing instances of cybersexism, in the academy. Reading our experience in the context of feminist insights on impurity and abjection, we assert the need to dismantle cybersexism targeting non-conforming academic knowledge, namely feminist. We also discuss the potentials of the cyberspace to provide opportunities for communal solidarity, as a source of empowerment for targets of academic cybersexism. Writing this text is an activist expression of voice and resistance, whereby we call our community to collective action and increased institutional support against sexism in academia, particularly in online spaces.